A dietary supplement to improve the quality of sleep: a randomized placebo controlled trial - Claustrat Bruno; Roy Pascal; Feugier-Favier Nathalie; Nicolas Alain; Noel-Baron Florence; Remontet Laurent; Cornu Catherine; Saadatian-Elahi Mitra; Kassaï Behrouz (BMC, 2010)
Abstract Background To evaluate the effect of a dietary supplement containing polyunsaturated fatty acids, in association with Humulus lupulus extract, on the quality of sleep using the Leeds sleep evaluation questionnaire (LSEQ) in subjects with moderate to severe sleep disorders. Methods Randomized placebo-controlled trial, in a Population-based setting. Participants were adult patients 25 to 65 years old with a chronic primary insomnia who volunteered for the study. The tested intervention consisted of two soft gelatine capsules per day, containing either the dietary supplement (active group) or olive oil (placebo group) for a month. Subjects could also volunteer for two ancillary studies on melatonin and actigraphy. Evaluation criteria included i) perception of the quality of sleep at the end of treatment using the LSEQ questionnaire, ii) sleep efficiency measured by one-week actigraphic movement measurement performed before and during the treatment in a subsample of subjects, iii) night melatonin and 6 sulfatoxymelatonin (aMT6S) urine rates in a subsample of subjects. Results The average of Leeds score was similar in both groups (p = 0.95). A marked improvement in the quality of sleep was observed in both placebo (62%) and active (65%) group (p = 0.52). The evolution of urinary melatonin, aMT6S, and of the Mel/aMT6S ratio showed no differences between the two groups. Sleep efficiency, as measured by actigraphy, improved similarly in both groups during the treatment period, from 72% to 76% and 75% in the active and placebo group respectively (p = 0.91). Conclusions The dietary supplement had neither effect on the perceived quality of sleep, nor on the melatonin metabolism and sleep-wake cycle. Trial registration: clinical trials.gov:NCT00484497